Molecular dynamics simulations of ch4 clathrate hydrate dissociation adjacent to hydrated silica surfaces - Bagherzadeh, A.; Englezos, Peter; Alavi, S.; Kumar, Rajnish; Ripmeester, John A. (7th International Conference on Gas Hydrates, 2011)
We use molecular dynamics simulations to study the decomposition of structure I CH4 clathrate hydrate exposed to water. Simulations are performed for a hydrate + water system and two related cases with the hydrate adjacent to hydrate silica layers. The simulations are in the NVE adiabatic ensemble paying careful attention to the non-isothermal nature of the hydrate dissociation process. The effects of mass and energy transfer on the hydrate dissociation rate are studied. The effect of the silica surface on the dissociation rate and mechanism are studied. It is observed that the hydrate layer decomposes more quickly in simulations where it is in contact with silica. The implications on decomposition of the hydrate in hydrate reservoirs adjacent to sand sediments are discussed.

Multiple H2 occupancy of cages of clathrate hydrate under mild condition - Lu, Hailong; Wang, Jianwei; Liu, Changling; Ratcliffe, Christopher I.; Becker, Udo; Kumar, Rajnish; Ripmeester, John A. (Journal of the American Chemical Society, 2012)
Experiments were carried out by reacting H(2) gas with N(2) hydrate at a temperature of 243 K and a pressure of 15 MPa. The characterizations of the reaction products indicated that multiple H(2) molecules can be loaded into both large and small cages of structure II clathrate hydrates. The realization of multiple H(2) occupancy of hydrate cages under moderate conditions not only brings new insights into hydrogen clathrates but also refreshes the perspective of clathrate hydrates as hydrogen storage media.